Academic Stress and Cyberslacking in Students: The Moderating Role of Emotion Regulation - Rinaldi, Martaria Rizky; Hardika, Jelang; Wiyoanti, Retvi (Jurnal Online Psikogenesis, 2024)
In the digital era, students increasingly rely on technology for academic purposes, yet they also face significant challenges such as cyberslacking—using the internet for non-academic activities during study time. This study investigates the role of emotion regulation in moderating the relationship between academic stress and cyberslacking among university students. A quantitative research design with a correlational approach was employed, involving 100 participants who completed online surveys assessing academic stress, emotion regulation, and cyberslacking behaviors. The Emotion Regulation Questionnaire (ERQ), Perception of Academic Stress Scale (PASS), and Cyberslacking Scale were utilized to gather data. Descriptive statistics, assumption testing, and moderation analysis were conducted using Jamovi software. The research findings indicate a significant positive relationship between academic stress and cyberslacking (Estimate = 0.69, p<0.01). Additionally, no relationship was found between emotion regulation and cyberslacking (p>0.05). Furthermore, the interaction between academic stress and emotion regulation on cyberslacking was also not significant (p>0.05). Specifically, students with lower emotion regulation exhibited a stronger association between academic stress and cyberslacking, while those with higher emotion regulation showed a reduced impact. These findings highlight the importance of effective emotion regulation in mitigating the negative effects of academic stress on cyberslacking.